Relationship between effort-reward imbalance, job satisfaction, and intention to leave the profession among the medical staff of Qom University of Medical Sciences† - Asgarian Azadeh; Abbasinia Mohammad; Sadeghi Roghayeh; Moadab Fatemeh; Asayesh Hamid; Mohammadbeigi Abolfazl; Heshmati Farahnaz; Mahdianpour Farzaneh (Sciendo, 2022)
The effort-reward imbalance (ERI) model claims that work that has the characteristics of high effort and low reward has a mutual defect between input and output and this imbalance may result in sustained and long-lasting results. This study aimed to investigate the relationship between the intention to leave the profession (ILP) and ERI and job satisfaction among the medical staff in Qom Province.